DEEP Study: Modeling Outcomes and Costs of Persistent Orofacial Pain. (January 2023) - Durham, J.; Breckons, M.; Vale, L.; Shen, J.
Persistent orofacial pain (POFP) affects patients' daily lives and can lead to significant costs for them and/or the health service provider. This partial economic evaluation examined costs and utilities experienced by individuals with POFP over a 24-mo period and used these data to populate the life course Markov model used to estimate costs and quality-adjusted life years (QALYs) from pain onset over an individual's life course while receiving usual health care. A total of 202 people receiving care for POFP were followed for 24 mo. Data were collected every 6 mo on pain-related disability (Graded Chronic Pain Scale dichotomized to low [0–IIa] or high [IIb–IV] pain-related disability states), health service utilization, and health-related quality of life measured by QALYs derived from the EQ-5D-5L. Unbalanced regressions were used to demonstrate how costs and QALYs varied according to participant characteristics with the results used to parameterize a Markov model. This probabilistic Markov model was used to estimate the outcomes for a cohort of POFP patients from age 25 y until death as determined by age- and sex-specific mortality rates. Across all time points, complete data were available from 129 participants. A high pain-related disability state led to significantly increased health care cost (£221; 95% confidence interval [CI], 87–355;P < 0.01) and a significant decrease in quality of life (mean difference, –0.08; 95% CI, –0.11 to −0.05;P < 0.0001) over a 24-mo period. The Markov model estimated that the average cost was £27, 317 (95% CI, 26, 558–28, 046) and the average lifetime QALYs were 17.54 (95% CI, 17.38–17.71). The modeling suggests that a cohort of POFP patients from age 25 y would only accrue 18 QALYs per person before death. POFP therefore exerts a considerable impact on health, and it is likely more effective care (pathways) could realize substantial gains in terms of both treatment outcomes and health care utilization. Knowledge of Transfer Statement: Despite a substantial number of consultations, individuals experiencing the care pathways in this study continued to have far from perfect health over their life course. The modeling suggests they would only experience 18 y in "perfect health." There is considerable scope to improve current care/outcomes and patient experience.